2013
DOI: 10.1002/dneu.22111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of survival of motor neuron (SMN) protein interaction with the mRNA‐binding protein IMP1 facilitates its trafficking into motor neuron axons

Abstract: Spinal muscular atrophy (SMA) is a lethal neurodegenerative disease specifically affecting spinal motor neurons. SMA is caused by the homozygous deletion or mutation of the survival of motor neuron 1 (SMN1) gene. The SMN protein plays an essential role in the assembly of spliceosomal ribonucleoproteins. However, it is still unclear how low levels of the ubiquitously expressed SMN protein lead to the selective degeneration of motor neurons. An additional role for SMN in the regulation of the axonal transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 48 publications
0
67
0
Order By: Relevance
“…However, an emerging idea is that the loss of additional function(s) of SMN unrelated to RNA splicing could co-contribute to SMA pathogenesis. In particular, it has been strongly suggested that SMN is involved in the trafficking and/or translation of target transcripts (Rossoll et al, 2003;Tadesse et al, 2008;Glinka et al, 2010;Peter et al, 2011;Hubers et al, 2011;Fallini et al, 2011Fallini et al, , 2014Yamazaki et al, 2012;Rathod et al, 2012;Sanchez et al, 2013). In this context, it is noteworthy to mention cross-species conserved genes able to mitigate the SMN loss-of-function defects (Dimitriadi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, an emerging idea is that the loss of additional function(s) of SMN unrelated to RNA splicing could co-contribute to SMA pathogenesis. In particular, it has been strongly suggested that SMN is involved in the trafficking and/or translation of target transcripts (Rossoll et al, 2003;Tadesse et al, 2008;Glinka et al, 2010;Peter et al, 2011;Hubers et al, 2011;Fallini et al, 2011Fallini et al, , 2014Yamazaki et al, 2012;Rathod et al, 2012;Sanchez et al, 2013). In this context, it is noteworthy to mention cross-species conserved genes able to mitigate the SMN loss-of-function defects (Dimitriadi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further hypotheses on the etiology of SMA have emerged by (i) the observation that the SMN protein is localized in axons of motoneurons (Zhang et al 2003) and (ii) the identification of a number of RNA-binding proteins interacting with SMN such as hnRNP R and Q (Rossoll et al 2002), FMRP (Piazzon et al 2008), HuD (Fallini et al 2011), IMP1 (Fallini et al 2013) as well as TDP-43 (Wang et al 2002;Tsuiji et al 2013), and FUS (Yamazaki et al 2012). The latter two are implicated in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…If there is a universal requirement for SMN, why are motor neurons selectively affected by its loss, and where does SMA first manifest? Does SMN dysfunction begin at the level of the motor neuron cell body, the axon, or the NMJ (11,12), and what effect does reduced SMN have on other components of the neuromuscular circuitry (13)?…”
mentioning
confidence: 99%